The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.5194/wes-2019-46
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Optimizing Wind Farm Control through Wake Steering using Surrogate Models based on High Fidelity Simulations

Abstract: Abstract. This paper aims to develop fast and reliable surrogate models for yaw-based wind farm control. The surrogates, based on polynomial chaos expansion (PCE), are built using high fidelity flow simulations combined with aeroelastic simulations of the turbine performance and loads. Developing a model for wind farm control is a challenging control problem due to the time-varying dynamics of the wake. Both the power output and the loading of the turbines are included in the optimization of wind farm control … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
19
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2

Relationship

4
3

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 26 publications
2
19
0
Order By: Relevance
“…The turbines attempts to align itself with the local inflow direction to optimize the power production, where the presence of wake effects may alter the local flow wind direction. Such behaviour was also described by McKay et al (2013) and shown in Hulsman et al (2019), where a optimization based on surrogate models showed that the second turbine should indeed align itself with the local wind direction. Archer and Vasel-Be-Hagh (2019) used LES to also show how turbines deep inside the farm could be intentionally yawed for improved performance.…”
Section: Introductionsupporting
confidence: 56%
“…The turbines attempts to align itself with the local inflow direction to optimize the power production, where the presence of wake effects may alter the local flow wind direction. Such behaviour was also described by McKay et al (2013) and shown in Hulsman et al (2019), where a optimization based on surrogate models showed that the second turbine should indeed align itself with the local wind direction. Archer and Vasel-Be-Hagh (2019) used LES to also show how turbines deep inside the farm could be intentionally yawed for improved performance.…”
Section: Introductionsupporting
confidence: 56%
“…The turbine attempts to align itself with the local inflow direction to optimize the power production, where the presence of wake effects may alter the local flow wind direction. Such behavior was also described by McKay et al (2013) and shown experimentally by Bartl et al (2018) as well as through the use of surrogate models based on high-fidelity simulations in Hulsman et al (2019), where the second turbine should indeed align itself with the local wind direction to optimize power production. Archer and Vasel-Be-Hagh (2019) used large-eddy simulations (LESs) to also show how turbines deep inside the farm could be intentionally yawed for improved performance.…”
Section: Introductionmentioning
confidence: 77%
“…A common form of wind farm control for power optimization is wake steering, in which a wake can be redirected away from a downstream turbine by inducing a yaw misalignment in the upstream turbine. Numerous studies on wake redirection have been performed by Fleming et al (2016), Gebraad et al (2016), Gebraad et al (2017), Jiménez et al (2010), Bossanyi (2018), and Munters and Meyers (2018), showing improved annual energy production in wind farms ranging between 2 % and 8 %. These investigations often assume a constant value of α to determine the trade-off between power losses due to yawing the upstream turbine and the power gain of the downstream turbine.…”
Section: Introductionmentioning
confidence: 99%
“…While many studies have performed proofs of concepts using only two or three turbines, 26,33,40,47,102,106,109,111,112,119,123,125,131,132,134,138,143,151,161–164 wake steering is more complicated in a wind farm. Fortunately, and in contrast to AIC, many of the lessons learned with a column of turbines still apply in larger arrays.…”
Section: Wake Management Techniquesmentioning
confidence: 99%